The public policy for urban water supply and sanitation services in Brazil: financialization, commodification and resistance perspectives - Britto, Ana Lucia; Rezende, Sonaly Cristina (Pontifícia Universidade Católica de São Paulo, 2017)
The article aims to analyze the public water supply and sanitation policy during the Brazilian Labor Party's administrations between 2007 and 2014, identifying, in the policy instruments, an ambiguity between a commodification logic and a logic of sanitation as a social right. It examines the growth of private sanitation companies in the period, showing their characteristics, and the recent changes promoted by the entry of international capital. Finally, it presents, as a counterpoint to what has been happening in Brazil, international cases of public management resumption, which demonstrate that privatization is not the only alternative, and that it is possible to reconcile efficiency and a logic of sanitation as a social right.